Beyond Punishment: A Criminological Analysis of Social Determinants of Criminal Behavior in Contemporary Society (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Criminal behavior has traditionally been examined through punishment-oriented frameworks that emphasize individual responsibility and legal accountability. Contemporary criminological scholarship increasingly demonstrates that crime is strongly influenced by social determinants operating within broader structural environments. This study analyzes the relationship between social determinants and criminal behavior in contemporary society using a normative criminological approach supported by conceptual, sociological, and criminological analyses. The findings indicate that socioeconomic inequality, social exclusion, educational deprivation, family dysfunction, structural discrimination, community disorganization, and technological transformation constitute significant factors contributing to criminal conduct. These determinants create criminogenic conditions that increase vulnerability to offending and facilitate the persistence of criminal activities across different social contexts. The study further finds that punishment-centered criminal justice policies possess limited effectiveness in addressing the underlying causes of crime, particularly regarding recidivism and long-term behavioral change. Preventive strategies emphasizing rehabilitation, social inclusion, educational development, community strengthening, and institutional reform demonstrate greater potential for sustainable crime reduction. Effective criminal justice systems therefore require integration between substantive criminal law, preventive social policies, and evidence-based criminological interventions to address both legal violations and their structural causes.